2021
DOI: 10.31742/ijgpb.81.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the diversity of grain phytic acid content in Indian rice landraces by multivariate genetic analyses

Abstract: Phytic acid (PA) acts as chelator of cationic mineral elements iron (Fe) and zinc (Zn) and obstructs their absorption in the human gut. We have evaluated a set of 162 traditional rice landraces for phytic acid phosphorus (PA-P), inorganic phosphorus (Pi) and total phosphorus (TP). Wide variability was observed for PA-P, Pi and TP ranging from 1.12 to 3 mg/g, 0.004 to 0.16 mg/g and 1.17 to 3.04 mg/g respectively. The mineral micronutrients, Fe and Zn were not in correlation with PA-P, Pi and TP implicating the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…The total phytic acid content in our study ranged from 0.067 to 0.777 g/100g. Longvah & Prasad [ 36 ] reported a phytic acid range of 0.331–0.407 g/100g for rice landraces from Arunachal Pradesh, while Gyani et al [ 58 ] reported a total phytic acid range of 0.117–0.334 g/100g in traditional Indian rice landraces. The present study consisted of many accessions with very low phytic acid contents, with the least in Kopak Ampe (IC458488×) (0.067 g/100g) and Borni (IC463883) (0.098 g/100g) followed by Kola Bora (IC464463) (0.104 g/100g).…”
Section: Resultsmentioning
confidence: 99%
“…The total phytic acid content in our study ranged from 0.067 to 0.777 g/100g. Longvah & Prasad [ 36 ] reported a phytic acid range of 0.331–0.407 g/100g for rice landraces from Arunachal Pradesh, while Gyani et al [ 58 ] reported a total phytic acid range of 0.117–0.334 g/100g in traditional Indian rice landraces. The present study consisted of many accessions with very low phytic acid contents, with the least in Kopak Ampe (IC458488×) (0.067 g/100g) and Borni (IC463883) (0.098 g/100g) followed by Kola Bora (IC464463) (0.104 g/100g).…”
Section: Resultsmentioning
confidence: 99%